The effectiveness of the training program designed on Power Point to provide the class Teacher students skills in designing electronic Educational blog - بركات, غسّان; حسامو, سهى; مسعود, أروى (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aimed to know the effectiveness of a training program designed using power point in providing the skills of designing an educational electronic blog for class teacher students. The sample consisted of (15) students from the third year / class teacher in the College of Education at Tishreen University. The research used a deferred pre / post / post cognitive test and a performance test. The research reached the following results: The effectiveness of the program designed using PowerPoint in providing students with the knowledge and performance side with the skills of designing the electronic blog. The effectiveness of the program designed using PowerPoint in retaining students' learning related to the skills of designing an electronic blog. There are statistically significant differences between the mean scores of the experimental group students on the cognitive and performance scale for designing an educational electronic blog in the pre and post measurements. In favor of telemetry. The researcher suggested: The necessity for educational institutions to benefit from the services provided by electronic blogs, and to work towards employing them in teaching. Conducting studies to identify obstacles to the use of e-learning blogs in university teaching.